English teachers’ perceptions of emergency remote teaching: Emotional attitudes, professional identity, and coping strategies - Huang, Fang; Zhao, Mingyan; Qi, Jiafu; Zhang, Ruyue (Frontiers in Psychology, 2023)
While the technology integration has been widely acknowledged, insufficient effort has been made to understand English teachers’ perceptions of emergency remote teaching (ERT). Given English is the primary foreign language in China and English teachers’ perceptions and adoptions of ERT impact the attainment of teaching and learning goals, this study inquired into experienced university English teachers’ emotional attitudes, perceptions of the reconstructed professional identity, and their strategies to cope with difficulties when conducting ERT in the Chinese English teaching context. Semi-structured interviews were conducted both online and face-to-face with five experienced universities English teachers in China. The findings indicated a trajectory of teachers’ attitudes toward ERT, namely, their attitudes were switched from doubt and rejection to fondness and attachment. Experienced English teachers adopted various strategies to cope with the difficulties and challenges they have encountered, including seeking support from their peers, students, and family, as well as self-regulated learning to sustain continuing professional development. During ERT, they have reconstructed their teacher identities. The study enriched peoples’ understandings of English teachers’ perceptions of the ERT by contextualizing the study in the Chinese educational context. Results can provide empirical evidence for policymakers and teacher trainers to make informed decisions regarding technical support and teachers’ continuing professional development.